Understanding Dushta Vrana: An Ayurvedic Perspective on Various Characteristics of Chronic and Complex Wounds (International Journal of Ayurveda and Pharma Research, 2024)
In the realm of Ayurveda, an ancient Indian system of medicine, the understanding of Vrana (wounds) extends far beyond mere physical injuries. Ayurvedic texts delve into the complex nature of chronic wounds and classify them under the umbrella term "Dushta Vrana". Dushta Vrana refers to non-healing, stagnant wounds resistant to conventional treatments, often requiring a multifaceted approach to facilitate the healing process.This review article aims to provide a comprehensive understanding of Dushta Vrana, shedding light on its diverse manifestations and underlying causative factors explained by Acharya Sushruta and Acharya Dalhana. By exploring the profound wisdom of Ayurveda, we can unlock potential solutions for the challenges posed by these persistent wounds.